Geopolitical risk and the rate of return of banks listed on the Vietnamese stock market - Phan Hồng Hải; Trần Trọng Huỳnh (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
Geopolitical Risk (GPR) plays a crucial role in shaping the stability and efficiency of listed banks in the stock market. This study analyzes the impact of GPR on the returns of banks listed on the stock exchange in the context of emerging markets, particularly in Vietnam. The study uses monthly data from January 2010 to December 2024, encompassing 19 banks listed on the Ho Chi Minh Stock Exchange (17 banks) and the Hanoi Stock Exchange (02 banks), with a total of 1,210 observations. The regression analysis results indicate that an increase in GPR is expected to decrease bank profits due to investor withdrawals and increased financial costs. Moreover, the impact of GPR on bank returns is lower compared to the effectssof market factors. This study contributes to the research field by providing evidence of the impactsof geopolitical risk on the banking industry and suggesting effective risk management strategies for policymakers and bank managers in Vietnam.